Use of L1 in the Iranian EFL Classroom - Mayni, Setareh Masoumi; Paramasivam, Shamala (S.Lakshmanan, 2021)
By reviewing the literature on the development of English language teaching methods in the last three decades, it is obvious that the idea of using the first language (L1) in the second language (L2) classroom has always been controversial. The history of language pedagogy and the role of the first language in foreign language learning generate debates in English as a foreign language. The teaching of English as a foreign language is growing every day in Iran, and as a result, the need for informing the best policy is getting more urgent. The principal intent of the current study, that investigates the use of L1 in the English classroom, is to determine teachers, students and policymakers' beliefs and attitudes towards the use of L1 in L2 classroom. The L1, in this case, is Farsi language and all the participants are native speakers of Farsi. One hundred and fifty students of the English Language Department at the elementary level at Tehran Institute of Technology are the participants of the study. They are all female and in their late teens or early twenties. The students and the teachers were surveyed by questionnaires and the researcher observed 10 classes and interviewed 3 teachers and 3 policymakers. The information gathered from the questionnaire was submitted to SPSS for analyzing the data, and the information gathered from the interview. Class observation check-list was used to triangulate the findings of the questionnaire. The results of this study indicate that teachers and students have different attitudes towards using L1 in the EFL classes. While students have a positive attitude, teachers have a negative attitude. The main reason mentioned by students for not being against the limited use of Farsi in their English class is that they believe using Farsi even in a limited sense can help them to understand difficult concepts. However, teachers believe in an English-only policy to be more exposed to the English language. Another finding of this study is that the functions of using Farsi by students or teachers in EFL classroom are: for explaining difficult parts, for managing the classroom, for explaining exam instructions, for explaining the two language differences, for checking comprehension, for seeking help from others, for joking with others, for making students relaxed and for presenting the meaning of new words. Given these findings, to match the student's and teachers'/policymakers' ideas about using L1 at the elementary level, an EFL teaching methodology that considers the use of Farsi, even in a limited way, is suggested.